A ANTIBODY MEDIATED IMMUNITY: ANTIBODY MEDIATED IMMUNITY - Budi Darmanta Sembiring (Universitas Methodist Indonesia, 2024)
Keeping the integrity and the individual balance needed an adequate immunity system. Therefore the immunity mechanism to the dangerous antigen consists of physical immunity and chemical, symbiosis with a normal flora bacteria, innate immunity with a specific immunity which is got, consist of humoral immunity and cell immunity (cell-mediated immunity). The antibody is the component of immunity that is gotten which protects the body from microorganism infection and the product which is toxic. Because of that, the interaction between antigen and antibody is very important and much used in vitro for diagnostic purposes. The use of this reaction in vitro between antigen-antibody is called serology.